The Effect of Work Life Balance and Work Discipline on Turnover Intention through Job Satisfaction (In Indomaret Employees in Barito Kuala Regency) - Rizqi Nugraha; Fanlia Prima Jaya (Hut Publication Business and Management, 2022)
This study is a quantitative study with the aim of knowing the effect of work life balance and work discipline on turnover intention through partial and simultaneous job satisfaction. In addition, this researcher also wants to know which value is the most dominant to influence the level of employee turnover intention. The population of this study were employees at 8 Indomaret stores, Barito Kuala Regency, amounting to 62 people. The sample taken in this study were 40 respondents, who were selected by the cluster random sampling method. Multiple linear regression was used to analyze the data. Data was collected by distributing online questionnaires. The program used to analyze the data is SPSS. This study shows that work life balance and work discipline affect turnover intention through partial and simultaneous job satisfaction.